A companion to the anthropology of education - Levinson, Bradley A., 1963-; Pollock, Mica, 1971- (Chichester, UK. : Wiley-Blackwell, 2011)
'A Companion to the Anthropology of Education presents a comprehensive and state-of-the-art overview of the field, exploring the social and cultural dimension of educational processes in both formal and nonformal settings. Explores theoretical and applied approaches to cultural practice in a diverse range of educational settings around the world, in both formal and non-formal contexts Includes contributions by leading educational anthropologists Integrates work from and on many different national systems of scholarship, including China, the United States, Africa, the Middle East, Colombia, Mexico, India, the United Kingdom, and Denmark Examines the consequences of history, cultural diversity, language policies, governmental mandates, inequality, and literacy for everyday educational processes'--
'Integrating work from several different national systems of scholarship, A Companion to the Anthropology of Education presents a comprehensive and state-of-art overview of the field of anthropology of education. Leading educational anthropologists examine everyday educational processes in culturally diverse settings, and the impacts on those processes of history, language policies, geographically specific problems and solutions, governmental mandates, literacy, inequality, multiculturalism, and more. Each contributor evaluates the key anthropological advances, arguments and approaches that inform the field's research. The Companion presents both theoretical and applied perspectives on important processes of education, in specific locations and worldwide'--
Includes bibliographical references and index.
Keywords: Educational anthropology